IJCM_426A: Use of Big Data for achieving Sustainable Development Goals (SDG) - A Review Paper. - Raina Ishaan; Rekha T (Wolters Kluwer Medknow Publications, 2024)
Background: The influence of AI and Big Data on the healthcare sector and health delivery systems provides a hopeful path to achieving the Sustainable Development Goals (SDGs) by way of improved decision-making and operational efficiencies. Methodology: A review of existing literature was carried out to evaluate the current landscape of AI applications in healthcare and its potential implications for SDG achievement. Results: Big data is at the center of health transformation, which, combined with artificial intelligence and Internet of Things, enables real-time processing and analysis of huge datasets. Big data enhances customization in marketing, streamlines operations in manufacturing and redefines healthcare by means of precision medicine. Big data also helps to drive changes in society through better public policy choices and steps taken to ensure sustainable development. It is through its analytic power that big data can identify obscure patterns and insights which can lead to pioneering solutions and strategic growth. Conclusion: Applying big data and AI strategically plays a crucial role in advancing the sustainable development agenda. However, we must exercise responsibility when utilizing the power of data. It is important to enforce strict measures of protecting data so as to avoid its misuse and also empower underdeveloped regions with relevant tools and capabilities for efficient data management. This way proactive moves will make sure that all people benefit from the information revolution, and it helps to drive global progress on SDGs.